Práticas do processo de cocriação em organizações que inovam abertamente - Alves, Juliana da Costa (2018)
Innovation is widely recognized as a collective act, and open innovation is recognized as the process of bringing together knowledge and resources with a community of partners to accelerate the innovation process. The purpose of this study was to verify the practices that organizations are using to increase client participation in the IA perspective. At the heart of open innovation is the ability to create an ecosystem where people, organizations and sectors promote co-creation (CHESBROUGH et al., 2014). There are three important types of open innovation: inbound (out-in), outbound (in-out) and inbound (PILLER; WEST, 2014). This study investigated the co-creation, also classified as the "entry" type of open innovation, non-pecuniary mode. In the non-pecuniary mode of entry of AI occurs the acquisition of external knowledge, without there necessarily being a compensation of external ideas and financial contributions. Regarding the objective, this research is exploratory. The technical procedures used were quantitative and qualitative. Regarding the choice of object, the multiple case study appears as the most appropriate for conducting this research. This method is based on the integration of several sources of information and allows the analysis of questions from different points of view (EISENHARDT, 1989). For the analysis and treatment of data, the content analysis was used, since it is a type of analysis that occurs through objective and systematic descriptions of the content, with the purpose of interpreting the same contents (MALHOTRA, 2001). The population of this research were organizations recognized for being openly innovating (inside and outside Brazil). Among the results, six practices stand out among the ones that most motivate clients' co-creation behavior in organizations: (1) "The innovation projects that are carried out are linked to the overall business strategy", (2) "The organization adapts its (3) "The organization has innovative practices that allow ideas to originate from the interaction of customers, suppliers, etc." (4) "Customers participate in the generation (5) "In the organization there are programs to attract ideas, suggestions and complaints" and (6) "The top management of the organization creates an environment conducive to Open Innovation". Another contribution of this study was the identification of the practices that most create barriers to clients' co-creation behavior. Among them, the high cost of implementing external ideas is what stands out the most. The other action that is evident is: "Some employees believe that if the organization pays more attention to external sources of knowledge, it may face resistance from some members of the internal technical group." And finally, the practice that stands out most as a barrier to co-creation behavior is number 6: "the legal department manifests a position of excessive protection as to intellectual property." Therefore, among the main contributions of the study, the framework of the actions that most motivate clients' co-creation behavior and barriers to this action stands out. One limitation of this study was the predominance of the IT sector in the sample. It is suggested that the co-creation behavior be analyzed in several sectors and in different degrees. In addition, it is also suggested to investigate empirically other motivators and other barriers that were not listed by theory, as well as whether the organization adopts yet another type of open innovation.